2013
DOI: 10.15241/jms.3.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Employment Preparation and Life Skill Development Initiatives for High School Students with Emotional and Behavioral Disabilities

Abstract: The quality of the therapeutic relationship and the personal characteristics of professional counselors are key determinants of positive counseling outcomes and decision making, and they are believed to be influenced by conscious and unconscious processes. Beliefs about the unconscious nature of altruism and self-interest among 25 mental health professionals were examined through a paradigmatic narrative analysis. Data from 19 semi-structured individual interviews, one focus group, 19 artifacts and participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Counselors may use nature‐based interventions to promote the mental and emotional well‐being of children (Feral, ; Robinson & Zajicek, ; Swank & Huber, ; Swank & Shin, in press; Swank & Swank, ) and to foster relationship building through game play and taking walks while talking (Guerney, ). In examining the effectiveness of a school gardening program, Robinson and Zajicek () found that students demonstrated improvement in self‐understanding and social skills.…”
Section: Nature‐based Interventionsmentioning
confidence: 99%
“…Counselors may use nature‐based interventions to promote the mental and emotional well‐being of children (Feral, ; Robinson & Zajicek, ; Swank & Huber, ; Swank & Shin, in press; Swank & Swank, ) and to foster relationship building through game play and taking walks while talking (Guerney, ). In examining the effectiveness of a school gardening program, Robinson and Zajicek () found that students demonstrated improvement in self‐understanding and social skills.…”
Section: Nature‐based Interventionsmentioning
confidence: 99%
“…These work sites were supervised by the transition coordinator who oversaw the connection of transition skills to the workplace. This supports previous research (Swank & Huber, 2013;Wagner, 1995;Wagner, D'Amico, Marder, Newman, & Blackorby, 1992; has found that programs need to allow students to complete school and enter the workforce with skills that will continue to support their success such as finding and maintaining jobs, independent living, and positive selfcare.…”
Section: How Are Emotional Disturbance Programs Narrowing the Graduation Gap Percentage Between Those Diagnosed With Emotional Disturbancsupporting
confidence: 88%
“…In a landmark inquiry, Ju and Zhang (2010) identified that as the number of students diagnosed (or undiagnosed) in these areas increases, the importance of finding programs becomes more critical. Other research (Swank & Huber, 2013;Wagner, 1995;Wagner, D'Amico, Marder, Newman, & Blackorby, 1992; has found that programs need to allow students to complete school and enter the workforce with skills that will continue to support their success such as finding and maintaining jobs, independent living, and positive self-care. Since the ED student is highly susceptible to these challenges, it becomes important to study ED programs in high school settings.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Addressing these global objectives, researchers offer varied perspectives regarding methods to arrive at them. Swank and Huber (2013) argue that "active engagement with community resources promotes opportunities to continue to learn pro-social behaviors and work skills, vocational education and aptitude beyond the school" (p. 78). Ramey (1984), however, believes the focus should be on the development of communication, and commitment to pursue personal goals.…”
Section: Literature Reviewmentioning
confidence: 99%